SQUID geomagnetic signal analysis and modelling of Schumann Resonances in the earth-ionosphere cavity - Kwisanga, Christian (Stellenbosch : Stellenbosch University, 2016)
Thesis (D.Phil)--Stellenbosch University, 2016.